Effects of Fuel Injector Seat Angle on Power, Torque, and Exhaust Emissions of a Single-Cylinder Four-Stroke Engine - Eko Surjadi; Wijoyo Wijoyo; Diama Rizky Septiawan (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to examine the relationship and comparison of motor performance based on different fuel injector angles in a fuel injection system, and to identify the optimal injector angle for improved engine performance. Fuel injection is a control technology that regulates the air–fuel mixture entering the combustion chamber with speed, precision, and proportional balance. An experimental method was employed using a 2020 motorcycle with a 108 cc engine. The tests conducted included torque, power, and exhaust emission measurements. Torque and power were measured using a dynamometer, while exhaust emissions were analyzed with a gas analyzer. The study compared injector mounting angles of 60°, 70°, and 80°. Results showed that torque increased significantly from low engine speeds (around 3000 rpm) and peaked between 3500–3750 rpm before gradually declining. Among the tested angles, the 80° injector position produced the highest torque across most speed ranges, reaching approximately 15 Nm at 3500 rpm. The 70° angle yielded moderate performance, while the 60° angle demonstrated the lowest torque, especially at medium to high speeds. Overall, the study found that increasing the injector angle enhances torque and power output, with average increases of 6.1% in power and 6.4% in torque.